(untitled) (Scientific journal of the Fergana State University, 2026)
This study determined the content of water-soluble vitamins and flavonoids in the roots and leaves of chicory (Chicorium intybus L.) using high-performance liquid chromatography (HPLC) and UV-spectroscopy. Vitamins were analyzed with acetate buffer and acetonitrile, while flavonoids were examined using phosphate buffer and acetonitrile. The differences in sample composition were demonstrated through diagrams and spectra. The results showed that the content of vitamins and flavonoids in the leaves was significantly higher compared to the roots, confirming the potential use of this plant as raw material for pharmaceuticals and biologically active supplements.